2011
DOI: 10.1172/jci57755
|View full text |Cite
|
Sign up to set email alerts
|

In vivo visualization and attenuation of oxidized lipid accumulation in hypercholesterolemic zebrafish

Abstract: Oxidative modification of LDL is an early pathological event in the development of atherosclerosis. Oxidation events such as malondialdehyde (MDA) formation may produce specific, immunogenic epitopes. Indeed, antibodies to MDA-derived epitopes are widely used in atherosclerosis research and have been demonstrated to enable cardiovascular imaging. In this study, we engineered a transgenic zebrafish with temperature-inducible expression of an EGFP-labeled single-chain human monoclonal antibody, IK17, which binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 33 publications
8
98
4
Order By: Relevance
“…Larvae were imaged at 20× magnifi cation using an Olympus IX50 epifl uorescent inverted microscope and cellSens Dimension software. The total number of BODIPY 576/589 C11-positive plaques was quantifi ed in a 438.6 × 330.2 m window along the caudal vein for a minimum of 25 larvae per MO per diet, as per published protocols ( 35,42 ).…”
Section: Vascular Lipid Accumulation Imaging and Quantifi Cationmentioning
confidence: 99%
See 1 more Smart Citation
“…Larvae were imaged at 20× magnifi cation using an Olympus IX50 epifl uorescent inverted microscope and cellSens Dimension software. The total number of BODIPY 576/589 C11-positive plaques was quantifi ed in a 438.6 × 330.2 m window along the caudal vein for a minimum of 25 larvae per MO per diet, as per published protocols ( 35,42 ).…”
Section: Vascular Lipid Accumulation Imaging and Quantifi Cationmentioning
confidence: 99%
“…Previous reports have demonstrated that zebrafish larvae become hypercholesteremic upon treatment with HCD, exhibiting increased total cholesterol and vascular plaques after 10 days of treatment ( 35,42,43 ). It is unknown, however, if hypercholesteremia in zebrafi sh can result from perturbation of gene expression.…”
Section: Mo Injection Disrupts Ldlr Expression Through Early Developmentmentioning
confidence: 99%
“…Cholesterol-fed zebra fish represent a novel animal model in which to study the early events involved in vascular lipid accumulation and lipoprotein oxidation [114,115]. Feeding zebra fish a high-cholesterol diet results in hypercholesterolaemia, vascular lipid accumulation, myeloid cell recruitment, and other pathological processes characteristic of early atherogenesis in mammals [113].…”
Section: Zebra Fishmentioning
confidence: 99%
“…Feeding transgenic zebrafish larvae an HCD for 2 weeks also resulted in oxidation-specific epitopes (OSE) accumulation and vascular inflammation, which increase vascular leakage and macrophage recruitment. 33 We created a transgenic zebrafish with conditional expression of EGFP-tagged single chain monoclonal antibody IK17, which targets malondialdehydemodified epitopes, to monitor the spatiotemporal accumulation of OSE. Furthermore, the expression of IK17-EGFP reduced vascular lipid accumulation.…”
Section: Zebrafish: a Unique Animal Model For The Study Of Atherosclementioning
confidence: 99%
“…Furthermore, the expression of IK17-EGFP reduced vascular lipid accumulation. 33 Thus, from a pathogenesis point of view, the initial events of atherogenesis are conserved between zebrafish and humans.…”
Section: Zebrafish: a Unique Animal Model For The Study Of Atherosclementioning
confidence: 99%